Labor markets and incarceration: the China shock to American punishment - Clegg, John (Criminology, 2023)
Studies have failed to show a positive effect of unemployment on incarceration despite reasons to expect such a relationship. We note that prior estimates have been muddied by the absence of substate data, a focus on prisons rather than on jails, limited measures of unemployment, and the fact that the health of the labor market is endogenous to incarceration. We instrument for local exposure to the rise of Chinese exports ("the China Shock") to estimate the effect of job loss on American incarceration. Marshaling a new data set of prisoners and jail inmates by race at the commuting zone level, we show that negative shocks to local labor markets led to significant increases in total incarceration rates for both Blacks and Whites. The effect seems to be driven by increased prison rather than jail populations. This estimate is invisible to ordinary least squares, which may help explain null results reported by past work. Counterfactual exercises suggest that the effect of job loss was punitively consequential. Had employment gains from the 1990s been preserved into the 2000s, the U.S. incarceration rate would have grown significantly less than it did.